Hepatoprotective activity of Chenopodium murale in carbon tetrachloride-induced hepatic damage in rabbits - Ullah, Aftab; Ahmad, Mahmood (Bangladesh Journal of Pharmacology, 2014)
The main purpose of this study was to determine the in vivo hepatoprotective activity of the ethanol extract of whole plant extract of Chenopodium murale (500 and 750 mg/kg; orally) in carbon tetrachloride-induced (0.75 mL/kg; subcutaneously) hepatotoxic rabbit. Silymarin (100 mg/kg/day orally) was used as a standard drug. Hepatotoxic rabbits boosted levels of serum glutamic oxaloacetic transaminase, serum glutamic pyruvic transaminase (SGPT), alkaline phosphatase and total bilirubin. Extracts of C. murale (both doses) proved to have hepatoprotective activity by reducing the elevated level of enzymes. Extract at a dose of 500 mg/kg revealed highly significant (p<0.001) results as compared to 750 mg/kg. Histopathological study of liver tissues additionally authenticated these findings. On the basis of our findings it is concluded that extracts of C. murale can be used in liver disorders.